Development of plasma burn-through simulation code and validation in SUNIST-2 and EAST - Ximan Li; Zichong Song; Yunxiao Wei; Runze Chen; Wenbin Liu; Zhengbo Cheng; Jinping Qian; Yi Tan; Long Zeng; Zhe Gao (Nuclear Fusion)
A full electromagnetic plasma burn-through simulation code has been developed to improve understanding of the plasma breakdown and initiation process in tokamaks, including spherical tokamaks. A 0D plasma model is adopted in the model, with only operation signals as input, such as current waveforms of central solenoid coils and poloidal field coils, prefill gas pressure and parameters for wall conditioning, which are determined before discharge experiments. The output includes the time evolution of the plasma current, electron temperature, ion temperature, and densities of gas compositions. The simulation code mainly contains three parts: circuit equations, energy balances, and particle balances. Eddy currents on toroidal passive conducting units of vacuum vessel and plasma current are calculated simultaneously by solving circuit equations. The use of eddy current waveforms and coil current waveforms enables calculation of the 2D space distribution of time-evolving poloidal magnetic field and flux, and consequently the plasma volume evolution can be calculated using the last closed flux surface. Energy balances and particle balances are used to solve the temperature and density evolution of fuel gas and impurities. The main procedures in energy balances and particle balances are ionization, recombination, charge exchange, radiation, and transport. Transport loss is estimated by perpendicular loss by Bohm diffusion and parallel loss along field lines, which is calculated using connection length and ion sound speed. The connection length is calculated using magnetic field line tracing with electromagnetic modeling. The code has been used to reproduce the time evolution of plasma current, electron density, flux loop data, and H _α or D _α data of plasma burn-through on SUNIST-2 spherical tokamak and EAST tokamak, and the simulated results are consistent with experimental measurements with the relative errors of the plasma current, loop voltage, and magnetic flux under 15%.